Smart Tourism-Based Marketing Strategies to Increase Visitor Numbers: A Case Study of Nimo Highland - Abdul Rahman Saleh; Harimukti Wandebori (Riviera Publishing, 2025)
The tourist sector in Indonesia is crucial for stimulating economic growth, especially via regional development and employment generation. As digitization alters tourist behavior, smart tourism has become a strategic necessity for destinations to maintain competitiveness in the digital age. This study examines how NiMo Highland, a swiftly expanding nature-based tourist destination in Pangalengan, Bandung Regency, may utilize smart tourism technology to enhance visitor numbers. The research used a qualitative descriptive methodology, incorporating strategic frameworks such the Ansoff Matrix, Marketing Mix (7Ps), PESTEL, and SWOT analysis to evaluate internal competencies and external environmental factors. Findings indicate that although NiMo Highland succeeds in organic digital visibility and experience offers, deficiencies persist in ticketing digitalization, third-party platform integration, and consistent event-based promotions. The study advocates for a smart tourism marketing strategy founded on three core components: (1) the integration of online travel agents (e.g., TikTok Go, Traveloka) to facilitate seamless bookings, (2) the deployment of RFID wristband technology to enhance visitor convenience and generate data-driven insights, and (3) the initiation of a signature annual event (Drone Show) to bolster brand positioning and seasonal attractiveness. These efforts seek to improve tourist engagement and operational efficiency while contributing to the wider discussion on digital transformation in nature-based tourism locations throughout Indonesia.